Hugo von Hofmannsthal et le néoplatonisme - Pauline Belvèze (Recherches Germaniques)
This article attempts to analyse the reception of Neoplatonism—that is to say the thinking of Plotinus and his pupils—by Hofmannsthal between 1890 and 1902. A new analysis of Hofmannsthal’s Ein Brief shows that this text—against what Pierre-Antoine Huré demonstrates in his own study—has more common features with the Neoplatonic metaphysics than with its mystics. The conception of the world that is sketched in the second part of the fictitious letter is closely linked to a conception of the human beings, which is gradually developed in the poems Ein Traum von großer Magie and Nox portentis gravida. A productive reception of Neoplatonic patterns in these poems makes a conciliation between Neoplatonism and Christianism possible. This evolution also offers a way to resolve the aesthetic dilemma that obliges Lord Chandos to give up his literary projects. Although no direct influence of Plotinus on Hofmannsthal can be claimed, his early work entails some similarities with Neoplatonic thought that help him to overcome his own contradictions and to give his aesthetics a new purpose.